Health-Related Quality of Life in Irritable Bowel Syndrome: A Systematic Review and Meta-analysis. (May 2020) - Cassar, Gillian E.; Youssef, George J.; Knowles, Simon; Moulding, Richard; Austin, David W.
Abstract : Irritable bowel syndrome (IBS) affects up to 20% of the global population and is associated with impaired health-related quality of life (HRQoL). This systematic review and meta-analysis aimed to investigate differences in HRQoL of those with IBS compared with healthy controls and to examine whether HRQoL improves following psychological intervention. Online databases were searched for articles from 2002 to 2017. Studies were screened and data extracted according to predetermined criteria. A total of 4, 154 citations were identified from which 36 were eligible for inclusion. Eight studies compared HRQoL of those with IBS ( n = 822) with that of healthy individuals ( n = 3, 809). Those with IBS suffered significant impairment across all HRQoL domains compared with healthy individuals, with the majority of effects (Cohen's d ) being moderate to large. Twenty-eight studies investigated HRQoL in IBS following psychological intervention ( n = 1, 308) relative to controls ( n = 1, 006). All HRQoL domains improved with large effects following treatment; however, maintenance of these effects was inconsistent. Those with IBS experience poorer HRQoL than the wider community; nevertheless, psychological interventions are associated with improved HRQoL across all domains. High-quality studies are needed to better inform gastroenterological nurses of which interventions are most efficacious in alleviating the burden of IBS, and which IBS subpopulations would benefit. Abstract : Supplemental Digital Content is Available in the Text.